Comparison of Chicken Varieties: Muscle Fiber Diameter, pH, Color, Tenderness in Pectoralis major Muscle - Katekhaye, M. Anita; Kumar, K. Shashi; Reddy, Kondal; Rao, V. Kessatva (Journal of Meat Science, 2018)
This study was undertaken to compare two varieties (Srinidhi and Vanaraja) at three age groups (16, 20, 24 weeks) in terms of muscle  fiber diameter, pH, color and tenderness qualities. A total of 210 birds reared up to age group 16, 20 and 24 weeks and slaughtered by  following standard procedure. Samples for muscle fiber diameter were taken from the middle parts of breast meat cut i.e. Pectoralis ma jor muscle. Muscle fiber diameter measured by calibrated micrometer under light microscope. Results of present study indicated variety,  age and sex significantly influence muscle fiber diameter, pH, tenderness and color. Vanaraja chicken observed significantly higher muscle  fiber diameter (µm) 43.43±3.98 than Srinidhi chicken 42.29±4.07. Vanaraja chicken recorded significantly (p≤0.05) higher pH 5.64±0.16,  (color coordinate) L* 54.98±1.09, a* 6.56±0.91, b* 35.17±1.97, shear force value (N) 12.40±0.71 than Srinidhi chicken pH 5.60±0.15, L*  53.49±2.01, a* 7.24±0.9, b* 35.05±1.09, shear force value 11.29±0.87. Male observed significantly higher pH, color coordinate L*a*b*,  shear force value than female. With age increased shear force values were associated with increased muscle fiber diameter. Results indicated that variety significantly affected physicochemical qualities of chicken.
Keywords: Srinidhi; Vanaraja; Color coordinate; Shear force value